Análise da alteração topográfica de superfície do esmalte dentário humano vestibular e lingual sob influência da idade - Straioto, Fabiana Gouveia (2006)
This study tested the hypothesis of that the surface topography of human enamel is influenced by the age and the face of the tooth organ. It was analyzed the human enamel surface topography divided in 3 groups of ages (n = 45) and subdivided in 2 sub-groups: I1V, not erupted in the vestibular face; I1L, not erupted in the lingual face; I2V, age between 20 and 40 years in the vestibular face; I2L, age between 20 and 40 years in the lingual face; I3V, age between 41 and 60 years in the vestibular face; and I3L, age between 41 and 60 years in the lingual face. The samples had been metallized and analyzed in laser interferometer (Microfocus Expert IV). The considered parameters of topography were: arithmetic mean of the heights of peaks and valleys (Sa), standard deviation of the heights of peaks and valleys (Sq), skewness (Ssk) and kurtosis (Sk). The values had been submitted to statistical analysis and applied the Kruskal-Wallis test, the Wilcoxon test and Spearman s correlation (p< 0.05). The results in µm were Sa: I1V- 1,36±0,58, I2V- 1,37±0,25, I3V- 1,26±0,72, I1L- 1,63±0,46, I2L- 1,90±1,28, I3L- 1,43±0,78; Sq: I1V- 1,98±0,94, I2V- 2,03±1,00, I3V- 1,84±1,09, I1L- 2,57±0,93, I2L- 3,01±1,83, I3L- 2,09±1,04. The values of Ssk and Sk of the samples had been presented in frequency, therefore they present distribution varying in intervals with positive and negative values. Ssk: of 87% (I2V and I1L), 60% (I1V and I2L) and 73% (I3V and I3L) of negative values indicating predominance of valleys and between 60 and 67% of the samples had presented values of Sk <3 indicating that for groups I1V, I2V, I3V, I2L, I3L predominated high peaks and low valleys. The results had shown that in the conditions of this study the surface roughness of the vestibular and lingual enamel of not erupted and erupted teeth with different ages, was modified with time of exposition in the oral cavity with alterations presents in the functional parameters of roughness: skewness (Ssk) and kurtosis (Sk). The kurtosis (Sk) was only one that presented correlation with the age, associated with the superficial morphologic analysis for SEM, however only the vestibular and lingual faces of not erupted teeth showed statistically significant difference in the Sq parameter (average quadratic roughness), while no difference was detected in the others values of Sq and Sa (average roughness).